Immunohistochemical changes in sigmoid colon after allogeneic and autologous bone marrow transplantation. Issue 4 (April 1995) - Forbes, G M; Erber, W N; Herrmann, R P; Davies, J M; Collins, B J
Abstract : AIM--To determine whether there are characteristic immunohistological changes in the colonic mucosa in acute graft versus host disease (GvHD). METHODS--Consecutive allogeneic (n = 11) and autologous (n = 11) bone marrow transplant recipients underwent endoscopic biopsy of sigmoid mucosa before transplant and on day 30 post-transplant. Immunohistochemical staining and quantitation of intraepithelial and lamina propria mononuclear cells were undertaken using a panel of monoclonal antibodies and a Streptavidin-biotin alkaline phosphatase staining technique. RESULTS--In the allogeneic group (nine of whom had clinical acute GvHD) there was a fivefold increase in lamina propria CD16+ mononuclear cells (3.1 +/- 4.3 to 17.0 +/- 12.2 per 100 lamina propria nucleated cells), compared with autologous transplant recipients in whom this rise was twofold (5.5 +/- 4.6 to 10.6 +/- 7.1 per 100 lamina propria nucleated cells). The CD16+ mononuclear cells had morphological appearances of tissue macrophages, but in neither the allogeneic nor autologous groups was there an increase in total macrophage numbers (CD14+). In patients with acute GvHD the lamina propria CD4+:CD8+ lymphocyte ratio fell (1.97 +/- 1.12 to 1.07 +/- 1.01), primarily because of a fall in the number of lamina propria CD4+ lymphocytes. In both allogeneic and autologous groups there was a fall in intraepithelial lymphocyte numbers, but there was no change in CD19+ (B cell), CD25+ (interleukin-2 receptor positive) or CD56+ (natural killer) cell numbers. CONCLUSION--Following bone marrow transplantation, there appears to be upregulation of lamina propria tissue macrophage CD16 (an Fc receptor for IgG), a change which is more noticeable after allogeneic transplantation and which may be related to the development of acute GvHD. In patients with acute GvHD there was a fall in the lamina propria CD4+:CD8+ lymphocyte ratio. If these changes are functionally important, they may have significant implications for understanding the pathogenesis of GvHD.